Robust multi-resolution analysis of polyhydroxyalkanoate biopolymers synthesized in a wastewater bacterium - Xinyu Chen; Yeonsoo Park; Zijian Wang; Gloria J. Zhou; Xinyue Mu; Eva Durance; Zhen Jia; Lynna Deng; George F. Wells; Fuzhong Zhang; April Z. Gu; Ludmilla Aristilde (Environmental Chemistry Letters, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Eco-grease from upcycling of waste oils: a formulation study for high-performance lubricants - N. A. F. Bashari; M. A. A. Aziz; M. A. Hairunnaja; T. M. A. B. N. Mu’Tasim (International Journal of Environmental Science and Technology, 2025)
The disposal of waste oils, particularly waste engine oil (WEO) and waste turbine oil (WTO), presents serious economic and environmental issues due to their high contamination and degradation levels, which reduce the efficiency of direct reuse or conventional recycling. This study investigates a practical approach for upcycling WTO and WEO into high-performance lubricating grease, providing a sustainable substitute for petroleum-based lubricants. The study includes five essential stages: waste oil collection, pre-treatment, characterization, grease formulation, and performance assessment. Following treatment, the viscosity, elemental content, and moisture levels of the oils complied with Department of Environment (DOE) and ASTM D5185 standards, confirming their viability as base oils. The formulated greases achieved NLGI grades of 2–3, oil bleed percentages within a ± 15%, and oil separation below 4%. They also exhibited low coefficients of friction (0.062–0.133) and wear scar diameters ranging from 415.65 to 866 μm. These results confirm that treated WTO and WEO can be converted into greases with performance comparable to conventional products, supporting reduced dependence on virgin base oils. The formulations were assessed under relevant ASTM and NLGI standards. Future work may explore additives or scale-up approaches to enhance long-term performance and market readiness.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Data driven food fraud vulnerability assessment using Bayesian Network: Spices supply chain - Y. Bouzembrak; N. Liu; W. Mu; A. Gavai; L. Manning; F. Butler; H.J.P. Marvin (Food Control, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Utilizing Cs-TPA/Ce-KIT-6 solid-acid catalyst for enhanced biodiesel production from almond and amla oil feedstocks - Sivarasan Ganesan; Velu Manikandan; Mohammed F. Albeshr; Saurav Dixit; Kwang Soup Song; Huang-Mu Lo (Process Safety and Environmental Protection, 2024)

Employing Piper longum extract for eco-friendly fabrication of PtPd alloy nanoclusters: advancing electrolytic performance of formic acid and methanol oxidation - Thamaraiselvi Kanagaraj; Velu Manikandan; Sivarasan Ganesan; Mohammed F. Albeshr; R. Mythili; Kwang Soup Song; Huang-Mu Lo (Environmental Geochemistry and Health, 2024)

Genetic diversity of the Atacama Desert shrub Huidobria chilensis in the context of geography and climate - K. Bechir Ferchichi; T. Böhnert; B. Ritter; D. Harpke; A. Stoll; P. Morales; S. Fiedler; F. Mu; J. Bechteler; C. Münker; M.A. Koch; T. Wiehe; et al. (Global and Planetary Change, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Adsorptive behavior of the rare earth elements Ce and La on a soybean pod derived activated carbon: Application in synthetic solutions, real leachate and mechanistic insights by statistical physics modeling - Raphael F. Pinheiro; Alejandro Grimm; Marcos L.S. Oliveira; Julien Vieillard; Luis F.O. Silva; Irineu A.S. De Brum; Éder C. Lima; Mu. Naushad; Lotfi Sellaoui; Guilherme L. Dotto; Glaydson S. dos Reis (Chemical Engineering Journal, 2023)

Mesoporogen free synthesis of CuO/TiO2 heterojunction for ultra-trace detection of catechol in water samples - Devaraj Manoj; Saravanan Rajendran; Mu. Naushad; Madhappan Santhamoorthy; F. Gracia; Matias Soto Moscoso; M.A. Gracia-Pinilla (Environmental Research, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Synthesis of a Novel Composite Sorbent Coated with Siderite Nanoparticles and its Application for Remediation of Water Contaminated with Congo Red Dye - Musa Alshammari; Maad F. Al Juboury; Laith A. Naji; Ayad A. H. Faisal; Hongshan Zhu; Nadhir Al-Ansari; Mu Naushad (International Journal of Environmental Research, 2020)
Re-use of the byproduct wastes resulting from different municipal and industrial activities in the reclamation of contaminated water is real application for green projects and sustainability concepts. In this direction, the synthesis of composite sorbent from the mixing of waterworks and sewage sludge coated with new nanoparticles named “siderite” (WSSS) is the novelty of this study. These particles can be precipitated from the iron(II) nitrate using waterworks sludge as alkaline agent and source of carbonate. Characterization tests using X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping revealed that the coating process was correctly achieved and siderite nanoparticles were planted on the surface of the composite sorbent. Interaction between Congo Red dye and composite sorbent was evaluated through a set of batch tests under the variation of agitation time, pH of aqueous solution, and sorbent dosage. The results proved that the prepared sorbent had a high ability in the treatment of water contaminated with Congo Red dye in comparison with previous studies and the maximum adsorption capacity reached to maximum value i.e. 9416 mg/g. The sorption process was governed by electrostatic attractions; however, Sips and Pseudo-second-order models described this process with coefficient of determination greater than 0.99. Graphic abstract

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

The carbon source separation from fermented sewage sludge for stimulation of denitrification and bisphenol A removal - R. Jia; L. J. Feng; G. F. Yang; J. Mu (International Journal of Environmental Science and Technology, 2019)

The Effect of a Medical Toxicology Inpatient Service in an Academic Tertiary Care Referral Center - Andrew M. King; Shooshan Danagoulian; Michael Lynch; Nathan Menke; Yijia Mu; Melissa Saul; Michael Abesamis; Anthony F. Pizon (Journal of Medical Toxicology, 2019)

Use of QSPR Modeling to Characterize In Vitro Binding of Drugs to a Gut-Restricted Polymer - Christine Taylor Brew; James F. Blake; Anita Mistry; Fengling Liu; Diana Carreno; Deidre Madsen; YongQi Mu; Martha Mayo; Wilhelm Stahl; David Matthews; Derek Maclean; Steve Harrison (Pharmaceutical Research, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

Cloning and expression analysis of Foxl2 during the reproductive cycle in Korean rockfish, Sebastes schlegeli - Wei J. Mu; Hai S. Wen; Ji F. Li; Feng He (Fish Physiology and Biochemistry, 2013)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

First records of the papaya strain of Papaya ringspot virus (PRSV-P) in French Polynesia and the Cook Islands - R. I. Davis; L. Mu; N. Maireroa; W. J. Wigmore; M. Grisoni; M. F. Bateson; J. E. Thomas (Australasian Plant Pathology, 2005)

Orientation of Arabidopsis thaliana KAT1 Channel in the Plasma Membrane - C.V. Mura; D. Cosmelli; F. Muoz; R. Delgado (The Journal of Membrane Biology, 2004)

Pleural empyema due to Salmonella enteritidis in a non-immunocompromised patient - M. Len Lope; P. Batalha; M. Sosa; F. J. Rodrguez-Gmez; A. Snchez-Muoz; E. Pujol; J. M. Aguado (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Psoas abscess in patients infected with the human immunodeficiency virus - V. Navarro Lpez; F. Lpez Garca; E. Gonzlez Escoda; J. Gregori Colom; A. Muoz Prez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Evaluation of groundwater availability and sustainable extraction rate for the Upper Santiago Valley Aquifer, Chile - Jos F. Muoz; Bonifacio Fernndez; Cristin Escauriaza (Hydrogeology Journal, 2003)

Cellular redox state and activating protein-1 are involved in ascorbate effect on calcitriol-induced differentiation - G. Lpez-Lluch; M. -V. Blzquez; R. Prez-Vicente; A. Macho; M. I. Burn; F. J. Alcan; E. Muoz; P. Navas (Protoplasma, 2001)

Resistance of Salmonella and Campylobacter Species to Antimicrobial Agents - B. Mirelis; G. Prats; T. Llovet; C. Muoz; F. Navarro (European Journal of Clinical Microbiology & Infectious Diseases, 1999)